2019
DOI: 10.1161/hypertensionaha.118.12097
|View full text |Cite
|
Sign up to set email alerts
|

Superimposed Preeclampsia Exacerbates Postpartum Renal Injury Despite Lack of Long-Term Blood Pressure Difference in the Dahl Salt-Sensitive Rat

Abstract: Preeclampsia results in increased susceptibility to hypertension and chronic kidney disease postpartum; however, the mechanisms responsible for disease progression in these women remain unknown. The purpose of this study was to test the hypothesis that 2 mechanisms contribute to the link between the maternal syndrome of preeclampsia and the increased postpartum risk of cardiovascular and renal disease: (1) increased T cells in the kidney and (2) a decreased NO:ET-1 (endothelin-1) ratio. Dahl S rats (a previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…PGE2 enhances mucosal blood flow and angiogenesis, and it accelerates epithelial wound repair and mucosal healing [ 49 ]. Endothelin (ET)-1 is a strong vasoconstrictor, and the increased release of ET-1 leads to dysregulation of the microcirculation [ 50 ]. It has been reported that ethanol stimulated the release of ET-1 in the gastric mucosa and caused a rapid, time-dependent increase in the level of ET-1 in plasma [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…PGE2 enhances mucosal blood flow and angiogenesis, and it accelerates epithelial wound repair and mucosal healing [ 49 ]. Endothelin (ET)-1 is a strong vasoconstrictor, and the increased release of ET-1 leads to dysregulation of the microcirculation [ 50 ]. It has been reported that ethanol stimulated the release of ET-1 in the gastric mucosa and caused a rapid, time-dependent increase in the level of ET-1 in plasma [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the RUPP model, BP and albuminuria recurred eight weeks after delivery, and no glomerular or tubular damage was detectable [31]. In Dahl salt-sensitive rats, glomerular and tubular injuries were present in female rats eight weeks after giving birth, detected as increased protein levels of nephrin and KIM-1 in the urine [43]. Together with our findings, these results support the evidence that persisting high blood pressure could be a cause for kidney damage observed in humans after preeclamptic pregnancy.…”
Section: Discussionmentioning
confidence: 98%
“…There are several animal models of preeclampsia and pregnancy-induced hypertension that demonstrate evidence of renal injury including the reduced uterine perfusion pressure [ 28 , 29 ], the Dahl S rat [ 30 , 31 ], the N -nitro- l -arginine methyl ester [ 32 ], and the transgenic renin-angiotensin model of preeclampsia [ 33 ]. There are very few actual models of pregnancy-related AKI.…”
Section: Discussionmentioning
confidence: 99%